Gastrointestinal bleeding in patients with hereditary hemorrhagic telangiectasia: Long-term results of endoscopic treatment - Manfredi, Guido; Crinò, Stefano Francesco; Alicante, Saverio; Romeo, Samanta; Berté, Roberto; Gandolfi, Silvia; Spinazzola, Angelo; Fiini, Michela; Forner, Pierangelo; Buscarini, Elisabetta (Endoscopy International Open, 2023)
Background and study aims This longitudinal prospective study evaluated the long-term outcome of endoscopic treatment of gastrointestinal bleeding in hereditary hemorrhagic telangiectases (HHT), its safety and outcome predictors.Patients and methods Consecutive patients with HHT and either anemia disproportionate to epistaxis or overt gastrointestinal bleeding received endoscopic treatment of gastrointestinal telangiectases with argon plasma coagulation (APC). Hemoglobin levels and transfusion requirements were evaluated before and after treatment. Treatment effectiveness was classified as: 1) complete: hemoglobin level during the follow-up ≥9 g/dL; 2) complete with recurrence: hemoglobin ≥9 g/dL for at least 12 months with subsequent drop to <9 g/dL; or 3) absent: no improvement of hemoglobin level. Adverse events (AEs) were classified as mild, moderate, severe or fatal. Correlations were searched between treatment outcome and demographic/genetic characteristics, number, size and site of telangiectases, and hepatic arterio-venous malformations grade.Results Forty-seven patients with HHT were enrolled. At median follow-up of 134 months (range 20–243 months), 41 of 47 patients showed treatment response (complete or with recurrence) after one (14/47) or more (27/47) endoscopic treatments. Median hemoglobin levels were 7.0 g/dL and 11.9 g/dL at baseline and at the end of follow-up, respectively. Transfusion requirement decreased from 22.8 to 7.3 red cell unit/year. A higher baseline number of telangiectases was associated with a lower chance of response (P=0.008). Only one severe AE (0.4%, jejunal perforation) was recorded.Conclusions Endoscopic treatment of gastrointestinal teleangiectases for gastrointestinal bleeding in patients with HHT is effective in the long term and safe.
Keywords: RFA and ablative methods; Small intestinal bleeding; Small bowel endoscopy